A resistance political culture: Basque Socialism and ETA’s terrorism (1984-2011) - Hidalgo García de Orellán, Sara (Huarte de San Juan. Geografía e Historia, 2018)
The aim of this article is to analyze the experience of Basque socialism on eta terrorism since 1984 until 2011. In 1984 took place the first murder of a socialist due to his militancy. In 2011 eta ceased its activities. For the analysis, the theoretical and methodological tools provided by the emotional turn are going to be used, and the main source will be oral history. The goal is to have a look on how ETA’s terrorist violence has impacted on the Basque socialist political culture and how the emotion of fear –the main emotion terrorism tries to spur– has worked on the members of this party.